New records, conservation assessments and distribution of Lamiaceae in Rio Grande do Norte, northeastern, Brazil - Soares, Arthur De Souza; Pastore, José Floriano Barêa; Jardim, Jomar Gomes (Phytotaxa, 2017)
This study presents nine new records and the conservation status of Lamiaceae species in Rio Grande do Norte State (RN), Brazil. The data obtained is based on fieldwork and examination of herbarium specimens. Thirty Lamiaceae species were recorded in RN, of which 16 are native to Brazil, nine are recorded for the first time for the state and one is new to science. The conservation assessments were based on IUCN geographic criteria: Area of Occurrence and Extension of Occurrence of each species. Among the native species, three were classified as Endangered, four as Vulnerable, three are of Least Concern, two are Near Threatened and four are Data Deficient. The highest number of Lamiaceae species, 14 altogether, is embraced by the phytogeographic domain Caatinga, a Seasonally Dry Tropical Forest, although less than 1% of this region is protected by conservation units. This study reveals the worrying conservation status of Lamiaceae in RN and the need for conservation actions, such as creating new conservation units and monitoring populations in the wild.